Perceived undersupply of local labour in the presence of unemployment: a case of selected Sundays River Valley citrus farms, 2013,Perceived labour shortages in the presence of unemployment - Chirara, Malon Tinotenda (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2015)
While skilled labour shortages are common in many countries, including South Africa, mainly due to a skills mismatch, the undersupply of unskilled labour was less expected, especially in developing countries with high unemployment. The thesis utilises data on perceived worker undersupply on selected citrus farms in the Sundays River Valley (SRV), located in the Eastern Cape Province of South Africa, collected in 2013, to analyse why unemployed residents, surprisingly, do not fill up vacancies on farms. In contrast to other labour markets, farm employment is not restricted by educational levels and as workers reported, with little training the various job tasks and skills required are easy and quick to grasp. At a time the government is trying to find ways of reducing unemployment, and the SRV Municipality (2012:29) reported approximately 42% unemployment, the question arises as to why the relatively low educated residents do not take advantage of the employment opportunities on farms. According to local workers and unemployed residents, the farm job was unattractive largely because of a combination of two factors: perceived relatively low salaries partly caused by the availability of migrant seasonal workers accepting lower remuneration and poor non-wage working conditions. The survey also found that farmers preferred migrant workers because they were more productive compared to their local counterparts who were, reportedly, characterised by high absenteeism and laziness, caused mainly by a reliance on social grants and alcohol abuse. Other reasons given for the unattractiveness of the farm job included the seasonal nature of farm employment, which left workers with no source of income in the offseason, the redundancy associated with farm tasks, perceived poor treatment of workers and lack of information on UIF and Provident funds to farm workers. To address problems associated with the dislike of farm work, seasonality of on-farm employment and the reportedly relatively low income, farm managers, the local municipality and the Labour Department could possibly be involved in creating more communal agricultural projects and help provide local community members to venture into supporting alternative careers within the Hospitality, Ecotourism and Conservation Industries through training programmes. Farm managers may need to consider improving their working relationship with workers in communication and when assigning tasks. Farmers and the local municipality could also consider investing in training programmes for the unemployed residents to equip them with technical skills that can improve their chances of finding jobs.
Keywords: Unemployment -- South Africa -- Sundays River (Eastern Cape); Citrus fruit industry -- South Africa -- Sundays River (Eastern Cape); Labor market -- South Africa -- Sundays River (Eastern Cape); Work environment -- South Africa -- Sundays River (Eastern Cape); Agricultural wages -- South Africa -- Sundays River (Eastern Cape); Agricultural laborers -- South Africa -- Sundays River (Eastern Cape); Seasonal labor -- South Africa -- Sundays River (Eastern Cape); Migrant agricultural laborers -- South Africa -- Sundays River (Eastern Cape); Personnel management -- South Africa -- Sundays River (Eastern Cape)